Development Of Smart Energy Monitoring Internet of Things System Based on App Inventor for Electric Energy Efficiency - I Wayan Dikse Pancane; I Nyoman Gede Adrama; I Wayan Sutama (Science and Technology Research Centre Universitas PGRI Semarang, 2025)
Electricity Demand for electrical energy in the food industry, including restaurants, continues to increase alongside the use of high-powered production equipment. This study aims to develop an Internet of Things (IoT)-based electrical load monitoring and control system using App Inventor at the Bakmi GM Denpasar production unit. The system consists of two components: a server (App Inventor) and a client (a microcontroller device based on a current sensor). Methods used include hardware design for power consumption data acquisition and development of a user interface for real-time monitoring and control. Test results show that the system can detect and manage electrical loads with 96.8% accuracy and reduce energy consumption by 18.5%, compared to before the system was implemented. These results demonstrate that integrating IoT technology into industrial electricity systems can significantly improve energy efficiency, reduce energy waste, and support environmental sustainability.